Qiyas dan Asas Legalitas (Telaah Penerapan Metode Qiyas pada Hukum Pidana Perspektif Hukum Islam dan Hukum Positif) - Najib, M. Ainun (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2022)
Abstract: Crime is growing very rapidly, far from leaving the law which is still guided by its standard editors. Qiyas method is needed to catch up. As a method of legal discovery, qiyas has been widely found in Islamic criminal law, but not with positive criminal law which in its application has a fairly large stumbling block in the form of the principle of legality as stated in Article 1 paragraph (1) of the Criminal Code, even the Draft Criminal Code is more explicit in mentioning the prohibition in the Criminal Code. Article 1 paragraph (2). This journal aims to explain the relationship between qiyas and the principle of legality in criminal law. The normative method is used in this journal by researching library materials, and supported by historical studies to add to the findings. Although there is a long debate, qiyas and the principle of legality basically need each other. Qiyas has been applied to Islamic criminal law, as well as in positive criminal law with a narrow meaning. Keywords: Qiyas, Analogy, Legality, Positive Law, Islamic Law